Security-enhanced live migration based on SGX for virtual machine - Yuan SHI; Huan-guo ZHANG; Bo ZHAO; Zhao YU (Tongxin xuebao)
The virtual machine may face the problem of information leakage in live migration.Therefore,a dynamic memory protection technique SGX was introduced and a security enhancement live migration method based on KVM environment was proposed.Firstly,on both sides of migration,a hardware-isolated secure execution environment centered SGX was built.It guaranteed the security of operations like encryption and integrity measurement and also ensured the security of private data.An encrypted channel to transfer migration data based on the remote attestation between the secure execution environments of both migration sides was constructed.And the mutual authentication of both sides’ platform integrity was realized.Finally,the security enhancement effect and did the experiment was analyzed.The results shows that the introduction of SGX won’t cause much negative effect to the migration performance.